Combination of the double-microcatheter technique and triaxial system in coil packing for visceral and renal artery aneurysms. (August 2019) - Goto, Taeko; Shimohira, Masashi; Ohta, Kengo; Suzuki, Kazushi; Sawada, Yusuke; Shibamoto, Yuta
Background: In coil packing for visceral artery aneurysms (VAAs), difficulties are sometimes associated with preserving the patency of the parent artery, particularly for wide-neck aneurysms. However, the double-microcatheter technique effectively prevents coil migration, while the triple-coaxial (triaxial) system is useful for reducing microcatheter kick-back. Purpose: To assess the feasibility of combining these two techniques in coil packing for VAAs. Material and Methods: Coil packing using the double-microcatheter technique and triaxial system was attempted for seven VAAs in six patients between August 2015 and January 2018. The technical success rate, packing density of aneurysms, complications related to the procedure, and occlusion status were evaluated. Technical success was defined as the completion of coil packing by immediate post-embolic angiography. The occlusion status was evaluated using time-resolved magnetic resonance angiography. Results: There were three renal, three splenic, and one anterior superior pancreaticoduodenal aneurysms. The median size of VAAs was 13 mm (range = 8–21 mm), with five being classified as wide-neck aneurysms. The completion of coil packing was confirmed for all VAAs and the technical success rate was 100%. The median packing density was 28% (range = 22–40%). There were no complications related to the procedure. The median follow-up period was 14 months (range = 8–24 months). In six VAAs that were followed up, there were three complete occlusions, three neck remnants, and no body filling; re-treatment was not required in any patient. Conclusion: The combination of the double-microcatheter technique and triaxial system is a feasible method of coil packing for VAAs.